Poor readers' retrieval mechanism: efficient access is not dependent on reading skill - Johns, Clinton L.; Matsuki, Kazunaga; Van Dyke, Julie A. (Frontiers in Psychology, 2015)
A substantial body of evidence points to a cue-based direct-access retrieval mechanism as a crucial component of skilled adult reading. We report two experiments aimed at examining whether poor readers are able to make use of the same retrieval mechanism. This is significant in light of findings that poor readers have difficulty retrieving linguistic information (e.g., Perfetti, 1985). Our experiments are based on a previous demonstration of direct-access retrieval in language processing, presented in McElree, Foraker, & Dyer (2003). Experiment 1 replicates the original result using an auditory implementation of the Speed-Accuracy Tradeoff method. This finding represents a significant methodological advance, as it opens up the possibility of exploring retrieval speeds in non-reading populations. Experiment 2 provides evidence that poor readers do use a direct-access retrieval mechanism during listening comprehension, despite overall poorer accuracy and slower retrieval speeds relative to skilled readers. The findings are discussed with respect to hypotheses about the source of poor reading comprehension.